(untitled) (World Conference on Agricultural and Earth Sciences, 2026)
The image of night occupies an important place in both Eastern and Western literary poetics as a universal artistic and philosophical symbol. In literary discourse, night is not only a temporal phenomenon but also a multidimensional aesthetic category associated with loneliness, silence, fear, spiritual contemplation, metaphysical anxiety, and existential consciousness. This article examines the philosophical and aesthetic functions of the image of night through a comparative analysis of Eastern and Western poetic traditions.